DISEÑO DE UN PLAN DE MANTENIMIENTO EN LA EMPRESA ROME-GOLD S.A. PARA REDUCIR EL ÍNDICE DE FALLOS DE LAS MÁQUINAS - Riera Chicaiza, María Elena (2023)
The current research is entitled the Design of a Maintenance Plan in Rome-Gold S.A. Company to reduce the failure rate of the machines, it is relevant due to the large number of unexpected stops of the machines, generating a decrease in the productivity of the company, despite the efforts of the maintenance department, so a preventive maintenance plan is proposed in order to mitigate the failures and improve the production process.